Metformin alleviates inflammatory response and severity rate of COVID-19 infection in elderly individuals - Xuguang Chen; Shengyi Shi; Hanwen Sun; Lei Zhou; Heng Wang; Yan Li; Eric Gilson; Yiming Lu; Lan Hu; Jing Ye (Scientific Reports)
Abstract To evaluate the relationship between metformin and the outcome of coronavirus disease 2019 (COVID-19) infection. The study included 413 patients with type 2 diabetes among the 5217 patients enrolled in a COVID-19 study, and analyzed whether receiving metformin therapy prior to infection was associated with risk of ICU admission, development of pneumonia and length of hospital stay. The study also examined the correlation between metformin treatment and levels of IL-6, CRP, serum ferritin (SF), lymphocyte, CD4 at admission, as well as the increase in open reading frame 1ab gene cycle threshold (ORF1abCT) after one week of hospitalization. There were no differences in age, sex, BMI, comorbidities, number of vaccine doses or eGFR between patients receiving and not receiving metformin therapy. In the ICU group, the proportion of patients not receiving metformin was 92.5%, significantly higher than the 69.2% of patients not admitted to ICU (p = 0.010). In the pneumonia group, the proportion of patients not receiving metformin was 78.6%, significantly higher than the 67.2% in the non-pneumonia group (p = 0.020). Compared with patients receiving no treatment, those receiving metformin had a shorter hospital stay (12.1 ± 5.9 days vs. 14.5 ± 8.2 days, p = 0.001). In the patients ≥ 60 years old, those receiving treatment had significantly lower levels of IL-6 (median, 12.3 pg/ml vs. 4.0 pg/ml, p = 0.026) and significantly higher levels of Lymphocyte (median, 1.2 × 109/L vs. 1.4 × 109/L, p = 0.015) compared with those not receiving treatment. However, for the patients under 60, there were no significant differences observed in IL-6 and Lymphocyte levels between those receiving treatment and those not. Metformin can reduce the severity of COVID-19 infection and attenuate the inflammatory response associated with COVID-19 infection.